Biblical Leadership Spirituality in Developing the Quality of Catholic Education - Sutami, Florensius; Nyaming, Fransiskus Gregorius; Simbolon, Subandri; Bhakti, Angga Satya; Kurniati, Yusi (Pascasarjana IAIN Pontianak, 2024)
Catechists preach the Bible through the practice of catechesis. The proclamation is carried out in a methodical and organic manner. Catechist actors, in particular, focus on evangelizing the general public, both clergy and laity. In the real-world development of the Christian faith, laypeople who become catechists have a complicated responsibility. Because they are directly involved in the lives of the people, they are at the forefront of the ministry work. They are also, in another sense, among people who share God's word with others. The lay catechists' experiences in life have become so ingrained in people's lives. The realities of today are extremely diverse. Even though they live in a time of globalization and modernity, there are still a lot of areas in which civilization has not been particularly developed. Border areas are in many cases being ignored, like places that are sometimes still harder to get to than the development of government centers, like roads that are hard to get to. Catechists face difficulties in providing services due to the scattered location of their service stations. To continue serving under the most difficult circumstances, the catechists need a spiritual spirit to support their efforts in developing religious education in this global world.